177 International Authorship Trends in Academic Neurosurgery and Effect of Double-Blind Review. (April 2023) - Chalif, Eric; Yue, John K.; Chillakuru, Yeshwant; Badani, Aarav; Aghi, Manish Kumar
Abstract : INTRODUCTION: There is a lack of data on international publication rates and whether reviewer biases exist that may affect diversity of authorship. METHODS: Articles published within Neurosurgery, Journal of Neurosurgery (JNS), and World Neurosurgery (WNS) were collected from 2000-2019. Country affiliation data was assigned and analyzed with respect to journal, year of publication, neurosurgical subspeciality, and relative impact. RESULTS: Across 23, 325 articles, lead authorship consisted of United States (42.9%, N = 10, 005), Japan (9.9%, N = 2, 305), China (9.3%, N = 2, 167), Germany (5.1%, N = 1, 187), South Korea (3.3%, N = 773), Italy (3.3%, N = 773), Canada (3.3%, N = 769), and other nations (22.9%, N = 5, 346). Rates of publications did not differ across United States, Asian countries, South/Latin American countries, or African countries pre- and post-initiation of double-blind review in Neurosurgery (p > 0.05). Annual percentage of publications showed highest relative decrease for the United States (-0.48% per year, r 2 = 0.194) and increase for China (0.87% per year, r 2 = 0.761). WNS published fewer articles from the United States compared to Neurosurgery or JNS (Mean difference [MD] -20.6%, p < 0.001), and more articles from Asian (MD +23.5%, p < 0.001), Latin/South American (MD +1.4%, p < 0.001), and African countries (MD +0.8%, p < 0.001). Unbiased co-authorship clustering by country demonstrated that certain countries were more likely to publish together based on geopolitical characteristics. CONCLUSIONS: There is a higher relative contribution to neurosurgery publications from authors in the United States compared to other countries. This effect is not due to potential biases in single-blind review, as evidenced by a natural experiment comparing authorship rates at Neurosurgery pre- and post-initiation of double-blind review in 2011. Additional research is needed to determine whether other biases contribute to differences in publication rates across countries.